Profit-Sharing - Moreau, Ernest (Relations industrielles / Industrial Relations, 1951)
SummaryThis brief report of the last Congress of the Boards of Trade of the Province of Quebec brings new suggestions for the study and application of this idea under way: profit-sharing.